A review: problems related to ash deposition and deposit formation in low-power biomass-burning heating devices - Dula, Małgorzata; Kraszkiewicz, Artur (Frontiers in Energy Research, 2025)
This literature review examines the problems associated with ash deposition and deposit formation in low-power heating devices and identifies possible solutions. The combustion of herbaceous biomass, especially that from waste from the agri-food industry, causes a large increase in the amount of mineral deposits in heating devices at a low melting point of the compounds they are composed of (particularly due to the presence of potassium (K), sodium (Na), and sulfur (S) compounds). They affect not only the formation of deposits and sediments but also the emission of fly ash, its handling, and the possibilities for its use and disposal. Problems related to ash depend on the content of alkaline oxides, which vary in proportion across different types of biomass. A dominant percentage of silicon dioxide (SiO2) is characteristic of ash from grass, rice husks, miscanthus, and straw pellets. Grass ash also contains a significant amount of potassium oxide (K2O), while ash from poplar wood, willow, and soy pellets is notable for its high calcium oxide (CaO) content. The deposition of ash volatiles and aerosols on boiler surfaces reduces heat exchange efficiency. The solution to the ash problems during combustion is the use of mineral additives, with kaolin being the most promising because of its very good ability to capture problematic alkali-containing compounds during combustion and convert them into potassium aluminium silicates with a high melting point. In addition, kaolin exhibits certain catalytic properties and can act as a carrier for active catalytic components that can be used in the processes of reducing nitrogen oxides (NOx) and particulate matter (PM). Natural carrier materials, such as kaolin clays, are of considerable practical importance as acidic catalysts. Methods for measuring the surface acidity of solids - including Brønsted and Lewis acid centres - which play a key role in catalysis are therefore of significant interest. The introduction of such additives increases the heating efficiency of the plant and at the same time reduces carbon monoxide (CO) and NOx emissions (which is inconsistently confirmed in the literature).